Assessing Minerals Status of Dairy Animals in South-West Zone of Punjab - Bhanderi, B. M.; Garg, M.R.; Sherasia, P.L. (Journal of Buffalo Science, 2015)
A study was carried out to assess dietary macro and micro-minerals status of milch buffaloes in Firozpur, Mansa and Muktsar districts, under South-West Zone of Punjab. Feeds and fodder samples were collected at random from various locations, following standard sampling procedure. The average calcium (Ca) content in straws was low (0.28%). Green fodders such as berseem (1.88%), chikori (1.26%), oat (0.45%), rye grass (0.56%) and mustard (1.34%) were found to be rich source of Ca. Concentrate feed ingredients such as mustard cake (0.68%), cottonseed cake (0.23%), rice polish (0.11%) and wheat flour (0.053%) were high to low in Ca. The phosphorus (P) content in crop residues and green fodders was 0.08 and 0.47 per cent, respectively. Concentrate feed ingredients were high (0.78%) in P. The magnesium content in roughages and concentrate feed ingredients was 0.31 and 0.41 per cent, respectively. The sodium content was low in concentrate ingredients (0.043%) and dry fodder (0.065%), but high in green fodder (0.63%). The sulphur content was adequate in green fodder (0.32%), whereas, crop residues (0.16%) and concentrate ingredients (0.18%), except mustard cake (0.33%) were deficient in sulphur; hence, its supplementation was necessary in the ration of milch animals. The cobalt was deficient in the diet of animals to the extent of 45 per cent; however, iron (average level > 500 ppm) and manganese (average level > 60 ppm) in most of the feed ingredients were adequate, with traditional feeding system. The average copper content was very low in straws (2.94 ppm) and moderate in green fodders (11.93 ppm). Concentrate ingredients were again low in copper (9.19 ppm). Zinc was deficient in most of the feedstuffs (average level<38 ppm) and needed to be supplemented for proper productive and reproductive functions. From the present study, it was apparent that the levels of certain minerals such as calcium, phosphorus, sulphur, zinc, copper and cobalt were inadequate, as per the prevailing feeding practices and requirement of buffalo yielding 10 kg milk (6% fat) per day. However, the levels of some other mineral elements such as magnesium, sodium, potassium, iron, manganese and selenium were found to be adequate in the South-West Zone of Punjab